Intensity Fluctuations of Flat-Topped Beam in Non-Kolmogorov Weak Turbulence: Reply - Gercekcioglu, Hamza; Baykal, Yahya (Optical Soc Amer, 2012)
In our recent publication, we have examined the intensity fluctuations of flat-topped beam in non-Kolmogorov weak turbulence [J. Opt. Soc. Am. A 29, 169 (2012)] in which our comparison of the scintillation indices in the Kolmogorov and in various non-Kolmogorov turbulences was based on the same structure constant, no matter what power law the non-Kolmogorov spectrum takes. In such choice of the fixed structure constant, which is also being used by many researchers in the field [Opt. Express 18, 451 (2010); Proc. SPIE 6747, 67470B (2007); Opt. Commun. 285, 880 (2012)], we have found that the variation of the scintillation index against non-Kolmogorov power law exhibits a peak at the worst power law, which happens to be smaller than the Kolmogorov power law of 11/3. Charnotskii commented [J. Opt. Soc. Am. A. 29, 1838 (2012)] on our paper. In this paper, in our to reply to Charnotskii's comment, we have re-evaluated the scintillation index of flat-topped beam in non-Kolmogorov weak turbulence by employing our recently reported equivalent structure constant [Opt. Lett. 36, 4554 (2011)] and re-compared the intensity fluctuations in Kolmogorov and in non-Kolmogorov turbulences. As the result of such re-comparison, the worst power law is observed to disappear. c 2012 Optical Society of America